The Influence of Cooperative Learning Models of Teams, Games Tournaments and Conventional Types and Learning Motivation on Student Learning Outcomes - Norma Asdika; Arsil Arsil; Kamal Firdaus; Muhamad Sazeli Rifki (JETL (Journal of Education, Teaching and Learning), 2025)
The problem addressed in this study is the low volleyball learning outcomes of eighth-grade students at SMP Negeri 26 Padang. This research aims to examine the effects of the Teams Games Tournament (TGT) and conventional teaching methods, as well as learning motivation, on students’ volleyball learning outcomes. The study employed a 2x2 factorial quasi-experimental design with purposive sampling, resulting in a total of 48 student participants. Instruments used include a questionnaire to measure learning motivation and a volleyball skills test to assess learning outcomes. Data were analyzed using ANOVA. The results showed: (1) the TGT method produced better volleyball learning outcomes than the conventional method, (2) there is an interaction effect between teaching methods and learning motivation on student outcomes, (3) highly motivated students achieved better results with TGT than with the conventional method, and (4) students with low motivation performed better with the conventional method than with TGT